Evaluasi Efektivitas ARTG sebagai Alternatif Operasi RTG Manual di Terminal Petikemas Semarang - Alfianto, Faizal Ridho; Mukhtar, Agus; Burhanuddin, Aan (CV. IRA PUBLISHING, 2025)
This study evaluates the effectiveness of Automated Rubber Tyred Gantry (ARTG) as an alternative to manual RTG operations at the Semarang Container Terminal. The research focuses on productivity (boxes/hour), maintenance cost efficiency (IDR/month), and workplace safety (number of incidents). A descriptive quantitative case study was conducted from March to May 2025. Results show that ARTG improved productivity by 11.25%, reduced maintenance costs by 46.5%, and recorded zero incidents compared to four incidents with manual RTG. All differences were statistically significant (p < 0.05). These findings indicate that ARTG enhances operational efficiency and safety in port operations. Gradual implementation of ARTG is recommended, considering digital infrastructure readiness, human resource training, and policy support.